Javier García. 2023. China, amenaza o esperanza. La realidad de una revolución pragmática. Ciudad de México: Akal. 200 pp. ISBN 9786078898121 - Ruiz, Ignacio Martín (Estudios de Asia y África, 2024)
Javier García. 2023. China, amenaza o esperanza. La realidad de una revolución pragmática. Ciudad de México: Akal. 200 pp. ISBN 9786078898121